Mapping the Path: Tracing Teacher Career Trajectories Towards Professional Teaching Standards - Legarde, Michael Angelo A. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
In the dynamic landscape of education, the quality of teaching remains a fundamental determinant of student success. Understanding teachers’ competence across multiple professional domains not only highlights their strengths but also identifies gaps that may limit instructional effectiveness and student learning outcomes. This study aims to examine the competence of public school teachers in the Philippines across the seven domains of the Philippine Professional Standards for Teachers (PPST), with the goal of identifying both areas of excellence and opportunities for professional growth. Employing a descriptive cross-sectional research design, the study surveyed 300 teachers from a range of large and small public secondary schools in Palawan, Philippines. Data were collected using a structured questionnaire aligned with the seven PPST domains and analyzed using mean scores to determine the levels of teacher competence. Results indicate that teachers generally demonstrate high to very high competence, with particular strengths observed in content mastery, classroom management, and professional commitment. Conversely, lower ratings were noted in domains such as differentiated instruction, actively seeking feedback, and implementing innovative teaching practices, signalling the need for targeted interventions. These findings underscore the importance of focused professional development programs that address specific areas of need, thereby fostering a more balanced, effective, and innovative teaching workforce. By addressing these gaps, policymakers and educational leaders can enhance teaching quality, ultimately supporting improved student learning outcomes and advancing the overall standards of Philippine public education.